ANALISIS PERUBAHAN PERILAKU KONSUMTIF PADA MAHASISWA PERANTAU (STUDI KASUS MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN) - Mauludin Mauludin; Okianna Okianna; Husni Syahrudin (Universitas Tanjungpura, 2021)
AbstractThis research was motivated by the association of overseas students which resulted in consumptive behavior. Migrating to make a shift in student lifestyle that changes due to different environments. This study was to determine and explain changes in the behavior of overseas students in consumptive behavior in students of economic education at FKIP Untan. This study uses qualitative methods with a case study approach, data collection techniques by interview and documentation. The object of this research were all students of FKIP Untan economic education who were traveling. Analysis of the validity of the data in this study used triangulation with data processing using the Miles and Huberman model. The results of this study were students of economic education who wandered into consumptive behavior as a result of advertisements in the city, caused by often hanging out in coffee shops to spend time and to play games with friends. Researchers also found that the consumptive behavior of students of economic education FKIP Untan was quite low.Keywords: Change In Consumptive Behavior, Overseas Students.